Underlying relationship between working capital management and profitability- a case study on GlaxoSmithKline Bangladesh Ltd. - Nafisa, Shamma (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.